1999
DOI: 10.1046/j.1469-0705.1999.14060393.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cerebral perfusion pressure changes in laboring women: effects of epidural anesthesia

Abstract: Objective To compare the effect of epidural anesthesia on cerebral perfusion pressure in laboring women. Study design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(22 reference statements)
0
9
0
1
Order By: Relevance
“…In an earlier study of cerebral perfusion pressure changes in laboring normotensive women by ultrasonography, 11) at the peak of a contraction and during pushing, cerebrovascular resistance was found to rise significantly, although cerebral blood flow did not change. In addition, preeclamptic patients in one study showed a global elevation of cerebral perfusion pressure and lower resistance in cerebral circulation than normotensive pregnant women.…”
Section: Discussionmentioning
confidence: 79%
“…In an earlier study of cerebral perfusion pressure changes in laboring normotensive women by ultrasonography, 11) at the peak of a contraction and during pushing, cerebrovascular resistance was found to rise significantly, although cerebral blood flow did not change. In addition, preeclamptic patients in one study showed a global elevation of cerebral perfusion pressure and lower resistance in cerebral circulation than normotensive pregnant women.…”
Section: Discussionmentioning
confidence: 79%
“…(6,(8)(9)(10)(11)(12)(13) These data from our study patients were plotted on the same axes as data collected longitudinally from 65 normal pregnant women followed through pregnancy at monthly intervals (12). Data points outside of the 5 th and 95 th percentile limits of the normative data were considered abnormal.…”
Section: Methodsmentioning
confidence: 99%
“…Williams and Wilson also investigated the effects of epidural anesthesia on cerebral perfusion pressure in laboring women115. In this study, patients with epidural anesthesia had lower calculated estimated cerebral perfusion pressure (eCPP = Vmean/(Vmean—Vdiastolic) × (mean BP—diastolic BP), where V is middle cerebral artery velocity and BP is blood pressure), resistance area product (RAP = mean BP/Vmean) and cerebral blood flow index compared with those in the non‐epidural group115.…”
Section: Intrapartum Ultrasoundmentioning
confidence: 96%
“…As a result of the above, pushing during the second stage with the Valsalva maneuver was therefore thought not to expose the patient to a greater risk of middle cerebral vasospasm than uterine contractions during the first stage of labor114. Williams and Wilson also investigated the effects of epidural anesthesia on cerebral perfusion pressure in laboring women115. In this study, patients with epidural anesthesia had lower calculated estimated cerebral perfusion pressure (eCPP = Vmean/(Vmean—Vdiastolic) × (mean BP—diastolic BP), where V is middle cerebral artery velocity and BP is blood pressure), resistance area product (RAP = mean BP/Vmean) and cerebral blood flow index compared with those in the non‐epidural group115.…”
Section: Intrapartum Ultrasoundmentioning
confidence: 99%